Spray‐Drying: Production of Additive‐Free Amorphous Nanoparticles with a SAW‐Based Microfluidic Spray‐Dryer (Adv. Mater. Technol. 6/2019). Issue 6 (11th June 2019) - Steinacher, Mathias; Du, Huachuan; Gilbert, Duncan; Amstad, Esther
Abstract : Spray‐drying is a widely employed, cost‐effective process to formulate solutions into solid particles of controlled sizes and compositions. In article number 1800665, Mathias Steinacher, Esther Amstad and co‐workers present a novel surface acoustic wave based microfluidic spray‐dryer that produces additive‐free amorphous particles by kinetically suppressing crystallization.